Smoking behavior, attitudes, and cessation counseling among healthcare professionals in Armenia - Movsisyan Narine K; Varduhi Petrosyan; Arusyak Harutyunyan; Diana Petrosyan; Armen Muradyan; Frances Stillman A (BMC, 2012)
Abstract Background Smoking cessation counseling by health professionals has been effective in increasing cessation rates. However, little is known about smoking cessation training and practices in transition countries with high smoking prevalence such as Armenia. This study identified smoking-related attitudes and behavior of physicians and nurses in a 500-bed hospital in Yerevan, Armenia, the largest cancer hospital in the country, and explored barriers to their effective participation in smoking cessation interventions. Methods This study used mixed quantitative and qualitative methods. Trained interviewers conducted a survey with physicians and nurses using a 42-item self-administered questionnaire that assessed their smoking-related attitudes and behavior and smoking cessation counseling training. Four focus group discussions with hospital physicians and nurses explored barriers to effective smoking cessation interventions. The focus group sessions were audio-taped, transcribed, and analyzed. Results The survey response rate was 58.5% (93/159) for physicians and 72.2% (122/169) for nurses. Smoking prevalence was almost five times higher in physicians compared to nurses (31.2% vs. 6.6%, p < 0.001). Non-smokers and ex-smokers had more positive attitudes toward the hospital's smoke-free policy compared to smokers (90.1% and 88.2% vs. 73.0%). About 42.6% of nurses and 26.9% of physicians reported having had formal training on smoking cessation methods. While both groups showed high support for routinely assisting patients to quit smoking, nurses more often than physicians considered health professionals as role models for patients. Conclusions This study was the first to explore differences in smoking-related attitudes and behavior among hospital physicians and nurses in Yerevan, Armenia. The study found substantial behavioral and attitudinal differences in these two groups. The study revealed a critical need for integrating cessation counseling training into Armenia's medical education. As nurses had more positive attitudes toward cessation counseling compared to physicians, and more often reported having cessation training, they are an untapped resource that could be more actively engaged in smoking cessation interventions in healthcare settings.